2021
DOI: 10.1016/j.sleep.2021.07.033
|View full text |Cite
|
Sign up to set email alerts
|

COVID-19 babies: auto-videosomnography and parent reports of infant sleep, screen time, and parent well-being in 2019 vs 2020

Abstract: Objective The COVID-19 pandemic has profoundly impacted families, yet studies on its effects on infants and their parents have thus far been sparse and based mostly on retrospective parent reporting. This study aimed to prospectively evaluate the impact of COVID-19 living conditions on infant and parent sleep, as well as infant screen exposure, parent daytime sleepiness, and parent depression levels, using multi-method assessment. Methods Infant and parent data collecte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 73 publications
0
4
0
Order By: Relevance
“…Pairwise comparisons indicated that daily screen exposure was significantly greater in 2020 for older infants (13-18 months old; mean difference ¼ 18,3 minutes, SE ¼ 4,6, p < .001), whereas differences were not significant for infants 12 months or younger. This study can describe that lockdown increase exposure of screen to children [13].…”
Section: Discussionmentioning
confidence: 88%
See 1 more Smart Citation
“…Pairwise comparisons indicated that daily screen exposure was significantly greater in 2020 for older infants (13-18 months old; mean difference ¼ 18,3 minutes, SE ¼ 4,6, p < .001), whereas differences were not significant for infants 12 months or younger. This study can describe that lockdown increase exposure of screen to children [13].…”
Section: Discussionmentioning
confidence: 88%
“…Additionally, a significant age-bytime interaction effect was found (SE ¼ .04). Pairwise comparisons indicated that daily screen exposure was significantly greater in 2020 for older infants (13-18 months old; mean difference ¼ 18,3 min, SE ¼ 4.6, p < .001), whereas differences were not significant for infants 12 months or younger [13]. A study by Nyström C et al (2020) reported during the COVID-19 pandemic, Swedish children's physical activity, time spent outside on weekdays and weekend days, and screen time significantly increased (+53; +124; +68; +30 minutes per day, respectively, all p ≤ .001) [14].…”
Section: Covid-19 Pandemicmentioning
confidence: 87%
“…Beyond the development of the WHO guidelines, sedentary screen time has received renewed interest recently as social distancing guidelines for the COVID‐19 pandemic forced many young children to stay home and required older children to engage in active screen time for education purposes. Amidst changing guidance, disruptions in formal childcare, and limited opportunities for active play, parents reported higher screen time for infants, toddlers, 40 and preschoolers compared to before the pandemic 41,42 . Indeed, children born during the pandemic have lower motor skills and developmental scores relative to children born before the pandemic 43 .…”
Section: Discussionmentioning
confidence: 99%
“…However, only nine found a significant difference in bedtime and/or wake-up time before and during confinement [17,18,42,79,82,132], one study did not find [117], and another found a significant difference only on weekdays [52]. One study found haste in sleep and wake-up time, however, subjects were 8.5 ± 4.6 months old [72]. In addition, one study found that the difference in the sleep duration between weekdays and weekends disappeared, while others that assessed the difference did not compare weekdays and weekends, only before and during quarantine [26].…”
Section: Bedtime and Wake Up Timementioning
confidence: 95%